Effects of supplemental hydrochloric acid and sodium bicarbonate on gastric acid secretion, digestive enzyme activities, intestinal microflora of early weaned piglets - LENG Xiang-jun; LI Xiao-qin; WANG Kang-lin; YANG Feng; ZHOU An-guo (浙江大学学报. 农业与生命科学版)
Thirty crossbred weanling piglets with an average initial weight of 5.25 kg, weaned at (28±1) d of age, were divided into five groups to determine the effect of hydrochloric acid (HCl) and sodium bicarbonate (NaHCO3) supplementation on gastric acid secretion, digestive enzyme activities, intestinal microflora. Piglets were fed corn-soybean meal-based diet without (control) or with 1% NaHCO3, 0.6% HCl, 2.4% HCl, 2.4% HCl+2.04% NaHCO3. The results showed that addition of 2.4% HCl induce gastric ulcer, repress the secretion of gastric acid and pepsin, reduce trypsin and amylase activities in duodelum digesta. Gastric acid and pepsin secretion, trypsin and amylase activities are not affected by addition of 0.6% HCl or 2.4% HCl+2.04% NaHCO3, but stomach pH and count of E. coli in colon are reduced, the activating-rate of pepsinogen is increased by the former, and count of E. coli in colon is increased by the latter; The secretion of gastric acid was improved, but stomach pH was increased by addition of 1% NaHCO3, which had no effect digestive enzyme activities in duodelum digesta, but increased the count of E. coli in colon, The results suggest that addition low level HCl (0.6%) to the diet of early weaned piglets reduce the amount of. E. coli in colon and scour incidence, but high level HCl (2.4%) and NaHCO3 (1%) are detrimental to the development of digestive tract.